The Strength Within: Evaluating Lecturers' Resilience Levels - Bahtiar, Rahayu Ahamad; Murshid, Siti Fairuz; Yahya, Husna; Yusof, Netty Yushani (New Advances in Business, Management and Economics Vol. 5, 2025)
Resilience is the ability to demonstrate both strength and flexibility during the change process while exhibiting minimal dysfunctional behavior. Staff’s commitment to organizational change and overall performance is positively influenced by resilience. Facing the challenges of new norms in the era of the COVID-19 pandemic requires to have a high level of resilience. The staff of many organizations must deal with a variety of challenges, changes, and uncertainties. In particular, lecturers in educational leadership and management training institutes must possess strong resilience to navigate these challenges effectively. This study aimed to explore the resilience level of lecturers in terms of their resilience level, profile, and differences in relation to their demographic background. A quantitative-based cross-sectional research design was employed for this study. A questionnaire was distributed to the lecturers from a training institute in Malaysia as the samples for this study using stratified random sampling. The results from a total of 200 respondents were analyzed. Data were analyzed quantitatively using Statistical Package for Social Sciences (SPSS) Version 18. There were seven domains of resilience explored in this study. Based on the finding, it was found that the overall resilience level of staff from this training institute was very high. Specifically, very high for four domains and high for the other three domains. It was also found that there was a significant difference in resilience level in relation to their retirement age. This study revealed that the lecturers from the training institute have a high level of resilience. This could stem from the existing working culture within the training institution itself, whereby it has become a norm for the lecturers to be agile, dynamic, and flexible in the ever-changing education system. The results showed that the lecturers’ resilience level was on par with what the institution required. However, the resilience level needs to be steadily improved for future endeavors due to unforeseen uncertainties. Therefore, this study may function as leverage for the management of these institutions to take necessary actions to further strengthen the resilience level among the lecturers, especially for the domains with a lower level.